2008
DOI: 10.1111/j.1745-6606.2008.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Rationality of Consumer Loan Choices: Revealed Preferences Concerning Interest Rates, Down Payments, Contract Length, and Rebates

Abstract: A choice-based conjoint experiment was employed to identify consumer preferences for automobile loan attributes. Respondents prefer loans with low interest rates and moderate contract lengths. Less important are high rebates and moderate down payments. Rebates are most important to choice when down payment is high. Even when choosing among interest-free loans, respondents do not prefer long terms, conflicting with traditional financial rationality. Respondents appear to focus attention on the first digit of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…Overall the literature suggests that consumers care most about the immediate implications, i.e., monthly repayment amount and loan duration, followed by total costs and interest rates. Consumers care less about auxiliary features such as rebates (e.g., Wonder, Wilhelm, & Fewings, 2008 for a US experiment). Notably consumers are likely to be biased by how information is presented (e.g., Estelami, 2001) and appear unable to integrate the different dimensions of a loan to an overall favorability judgment.…”
Section: A Process‐based Review Of Phenomenological Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall the literature suggests that consumers care most about the immediate implications, i.e., monthly repayment amount and loan duration, followed by total costs and interest rates. Consumers care less about auxiliary features such as rebates (e.g., Wonder, Wilhelm, & Fewings, 2008 for a US experiment). Notably consumers are likely to be biased by how information is presented (e.g., Estelami, 2001) and appear unable to integrate the different dimensions of a loan to an overall favorability judgment.…”
Section: A Process‐based Review Of Phenomenological Perspectivesmentioning
confidence: 99%
“…Overall, consumers seem to prefer loans of moderate or short length (Wonder et al., 2008 for the US) and to want to repay loans as quickly as possible, including a preference for repaying more at an early stage and less at a later stage (Hoelzl, Kamleitner, & Kirchler, 2011 for Austria). Interestingly this preference for “getting it over with quickly” persists even if it would make economical sense to owe more for longer, i.e., in the absence of interest (Hoelzl et al., 2011; Wonder et al., 2008). A force potentially counteracting this preference is the established preference to somewhat match the life or usage time of a financed object with the repayment period (Hirst, Joyce, & Schadewald, 1994).…”
Section: A Process‐based Review Of Phenomenological Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This mode of decision making reflects a desire by consumers to simplify the complexity of their decision environment by focusing on a subset of the available information as a basis of their decision making. For example, in a loan transaction, a consumer may focus on the monthly payments and ignore other aspects of the offer such as the interest rate, processing fees, and closing costs (e.g., Estelami, ; Wonder et al ., ; Frank, ). Lease/buy/rent : Given that leasing, buying, and renting are three common approaches to obtaining long‐term access to large‐ticket assets such as homes and automobiles, this form of decision error reflects choosing one option (e.g., leasing), when another option (e.g., buying through financing) may be more economical (Wonder et al ., ; Smith et al ., ). Time value of money : Not recognizing the significance of interest expenses that may accumulate over time or not realizing that cash devalues with the passage of time. For example, the consumer may not pay attention to the interest payments that accumulate on credit card debt if balances are not paid off fully (e.g., Thaler, ; Benartzi and Thaler, ; Ellen et al ., ). Risk misperceptions : Overestimating unlikely risks or underestimating significant risks.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wonder et al . () utilized conjoint analysis to determine the drivers of automobile loan decisions. They found that decisions with respect to loans defy rational economic prescriptions, such that consumers prefer shorter to longer payment cycles even in cases of 0 per cent interest loans.…”
Section: Challenges In Quantifying the Quality Of Consumer Financial mentioning
confidence: 99%